Pengaruh Game Online, Penggunaan Sosial Media, Penggunaan ChatGPT, dan Literasi Digital terhadap Minat Belajar Mahasiswa - Halim, Fidelia Vanessa; Setiawan, Amelia; Djajadikerta, Hamfri (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Current learning intention is influenced by various factors and trends in society, especially technological developments. Some factors that can affect students' learning intention include various digital platforms such as online games, social media, and ChatGPT technology. Therefore, digital literacy is also needed by students to bridge technology with their learning intention. The aim of this study is to determine the influence of online games, social media, ChatGPT, and digital literacy on students' learning intention. A quantitative method was used by distributing modified scales of the variables online to 119 students. The data were analyzed using multiple regression tests. The results show that, simultaneously, online games, social media, ChatGPT, and digital literacy affect students' learning intention. When tested partially, only digital literacy has a significant influence on learning intention. This study reinforces the importance of strengthening digital literacy programs to help students develop the ability to use digital technology wisely and effectively in order to increase their learning intention in higher education. Keywords: ChatGPT, Digital Literacy, Learning Interest, Online Games, Social Media, Student.